A polyether amine modified metal organic framework enhanced the CO2 adsorption capacity of room temperature porous liquids. Issue 87 (17th October 2019) - Zhao, Xuemei; Yuan, Yihui; Li, Peipei; Song, Zenjun; Ma, Chunxin; Pan, Duo; Wu, Shide; Ding, Tao; Guo, Zhanhu; Wang, Ning
Abstract : A room-temperature MOF-based porous liquid was prepared and showed an outstanding CO2 uptake capacity. Abstract : Based on both the compatibility principle of similar polymeric structures and the steric interaction, a polyether amine (D2000) modified MOF (UIO-66) was dispersed into an ionic liquid with a polyether structure to form a new porous liquid (called the UIO-66-liquid) at room temperature. This unique UIO-66-liquid showed an outstanding CO2 uptake capacity among the existing porous liquids.